A metagenomic survey of lamb's pre- and post-weaning fecal microbiomes. Issue 1 (1st January 2020) - Albakri, N. N.; Bouqellah, N. A.; Shabana, I. I.
ABSTRACT: Weaning is known to be the most stressful and critical transition experienced by lambs, it affects the structure of the gastrointestinal tract microbiomes, which significantly influences the lamb's health and performance. The present study identified the structure of lambs' pre- and post-weaning fecal microbiomes to define the implications of the weaning transition. Illumina MiSeq yielded a total of 5169 sequence reads per fecal sample ranging from 106 to 2028.  Before weaning, the taxonomic analysis indicated that the phylum Firmicutes dominated other bacterial phyla at a rate of (≤52.47%), followed by Proteobacteria at a rate of (≤52.00%). On the contrary, the phylum Firmicutes (≤93.01%) tended to increase, while the phylum Proteobacteria tended to decrease (≤26.83 %) after weaning. At the genus level, twenty-eight genera assigned to three phyla were detected in pre-weaned lambs; meanwhile, thirty-three genera assigned to four phyla were identified in post-weaned lambs. These findings suggested that weaning significantly influenced the diversity and the abundance of lambs' fecal microbiota.